Kontribusi Kepemimpinan Atasan Langsung Terhadap Prestasi Kerja Pegawai Dinas Pendidikan dan Kebudayaan Kabupaten Agam - Restiyandi, Rhozi; Anisah, Anisah; Marsidin, Sufyarma; Susanti, Lusi (Jurnal Family Education, 2024)
This research was conducted by looking at the low contribution of direct superior leadership to employee work performance. The aim of this research is to obtain information about the contribution of direct superior leadership to the work performance of employees of the Agam Regency Education and Culture Service. The population of this study was 72 people and the number of samples for this study was 45 employees of the Agam Regency Education and Culture Service. The data collection technique used for research is instruments. Data analysis can determine the average percentage of each variable. Based on the analysis of research data, it can be concluded that there are several conclusions, namely (1) The leadership of direct superiors at the Agam Regency Education and Culture Service can be categorized as good with an average score of 88.86% (2) The work performance of employees at the Agam Regency Education and Culture Service can be categorized as high at 81.06%. (3) At the Agam Regency Education and Culture Service there is a direct leadership contribution to employee work performance at a significant level of 1%, with a regression coefficient of 27.6% and 72.4% influenced by other factors. It can be concluded that the contribution of superior leadership directly influences employee work performance.